2004
DOI: 10.4028/www.scientific.net/msf.449-452.737
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dissolution Properties of Phosphate Glasses for Glass Fertilizer

Abstract: For usage of glass fertilizer, physical and dissolution properties were investigated according to variation of the SiO2 and K2O contents in silicate glasses. In glass forming region, K2O/P2O5 0-0.24, SiO2/(SiO2+P2O5) 0-0.29 and CaO/P2O5 0-1.00 were fabricated as clear glass in K2O-CaO-SiO2-P2O5 glass system. The glass transition temperature (Tg) and softening temperature (Ts) were gradually shifted to the higher temperature range according to increase of SiO2 contents. The K2O contents, which could cause the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…The use of phosphate glasses can be considered towards controlled-release fertilizers because they offer the possibility of complete dissolution in aqueous environments depending on their chemical compositions, in addition to their ability to participate in the biological processes of living organisms [ 23 , 24 , 25 ]. Furthermore, in a recently published study [ 26 ], we have shown that glass fertilizers application on wheat ( Triticum durum L.), compared to NPK treatment, significantly increased growth, physiological parameters, and yield, which means that these fertilizers constitute a potential substitute for conventional fertilizers due to their positive effect on wheat production and can be used in practice as an eco-friendly controlled-release fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…The use of phosphate glasses can be considered towards controlled-release fertilizers because they offer the possibility of complete dissolution in aqueous environments depending on their chemical compositions, in addition to their ability to participate in the biological processes of living organisms [ 23 , 24 , 25 ]. Furthermore, in a recently published study [ 26 ], we have shown that glass fertilizers application on wheat ( Triticum durum L.), compared to NPK treatment, significantly increased growth, physiological parameters, and yield, which means that these fertilizers constitute a potential substitute for conventional fertilizers due to their positive effect on wheat production and can be used in practice as an eco-friendly controlled-release fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, scientists had investigated phosphatebased glasses for various technological applications including sealing materials, solid-state electrolytes [2,3], radioactive waste containment [4], laser technologies, medical applications such as degradable tissue and bone scaffolds [5], and agro-fertilizers with controlled solubility [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the potential of phosphate glass to be glass fertilizer has been extensively studied [1]. Glass fertilizer is a type of glass matrix embedded with several macro and micro elements such as phosphorus, potassium, calcium and magnesium which is important for plant developments [2].…”
Section: Introductionmentioning
confidence: 99%